# Find the value of k if x^2 + kx - 6 = (x - 2)(x + 3).

### 2 Answers | Add Yours

Given the equation.

x^2 + kx -6 = (x-2)(x+3)

We need to find the values of k.

First we will simplify the right side by opening the brackets.

==> x^2 + kx -6 = x^2 +3x -2x - 6

==> x^2 + kx -6 = x^2 + x - 6

Now we will add 6 to both sides.

==> x^2 + kx = x^2 + x

Now we will subtract x^2 from both sides.

==> kx = x

Now we will divide by x .

==> k = x/x = 1

**==> Then the values of k = 1.**

We have to find k for x^2 + kx - 6 = (x-2)(x+3)

x^2 + kx - 6 = (x-2)(x+3)

=> x^2 + kx - 6 = x^2 - 2x + 3x - 6

=> x^2 + kx - 6 = x^2 + x - 6

=> x^2 - x^2 - 6 + 6 + kx = x

=> kx = x

=> k = 1

**The required value of k is k = 1 **